Investigation on sub-interface crack problems in composite materials with aerospace engineering applications - Tan, Christopher Aguirre (Nanyang Technological University, 2023)
The aviation sector frequently uses composite materials in airplane structures. The sub-interface of the composite materials will start to crack under specific loads and further research is required to fully understand the impact of cracks between layers since they are difficult to detect. Unexpected crack formation is possible, and if they are missed during inspection, the structure may fail catastrophically. Knowing a crack's stress intensity factor is essential because if it exceeds the material's fracture toughness, the crack will begin to propagate. As the physical surroundings of the fracture, such as the crack's position in relation to the joint, and material properties such as Young's modulus and Poisson ratio, can raise or reduce the stress intensity factor, further investigation is necessary. Ansys static structural software is an excellent instrument for investigating these effects since data can be simply analyzed rather than performing physical tests to obtain findings. This report will evaluate a 2D parametric investigation of the normalized stress intensity ratio and establish relationships between material characteristics, crack orientation with respect to a joint and the crack stress intensity factor.